Candidatus Nitrosocaldus cavascurensis, an Ammonia Oxidizing, Extremely Thermophilic Archaeon with a Highly Mobile Genome - Abby, Sophie S.; Melcher, Michael; Kerou, Melina; Krupovic, Mart; Stieglmeier, Michaela; Rossel, Claudia; Pfeifer, Kevin; Schleper, Christa (Frontiers in Microbiology, 2018)
Ammonia oxidizing archaea (AOA) of the phylum Thaumarchaeota are widespread in moderate environments but their occurrence and activity has also been demonstrated in hot springs. Here we present the first cultivated thermophilic representative with a sequenced genome, which allows to search for adaptive strategies and for traits that shape the evolution of Thaumarchaeota. Candidatus Nitrosocaldus cavascurensis has been cultivated from a hot spring in Ischia, Italy. It grows optimally at 68°C under chemolithoautotrophic conditions on ammonia or urea converting ammonia stoichiometrically into nitrite with a generation time of approximately 23h. Phylogenetic analyses based on ribosomal proteins place the organism as a sister group to all known mesophilic AOA. The 1.58 Mb genome of Ca. N. cavascurensis harbors an amoAXCB gene cluster encoding ammonia monooxygenase, genes for a 3-hydroxypropionate/4-hydroxybutyrate pathway for autotrophic carbon fixation, but also genes that indicate potential alternative energy metabolisms. Although a bona fide gene for nitrite reductase is missing, the organism is sensitive to NO-scavenging, underlining the potential importance of this compound for AOA metabolism. Ca. N. cavascurensis is distinct from all other AOA in its gene repertoire for replication, cell division and repair. Its genome has an impressive array of mobile genetic elements and other recently acquired gene sets, including conjugative systems, a provirus, transposons and cell appendages. Some of these elements indicate recent exchange with the environment, whereas others seem to have been domesticated and might convey crucial metabolic traits.